UNOFFICIAL VIEWS OF BULGARIAN OFFICIALS AND INSTITUTIONS ON THE MACEDONIAN IDENTITY AT THE END OF THE XIX AND THE BEGINNING OF THE XX CENTURY (Annual of the Faculty of Philosophy in Skopje, 2009)
This article aims to present several statements of Bulgarian intellectuals, officials and politicians concerning the Macedonian identity. These statements confirm beyond any doubt that the official representatives of Bulgarian institutions were well aware of the existence of a separate Macedonian identity, regardless of the fact that they considered Macedonians a part of the Bulgarian nation. The examples mentioned in this article oppose the position of the official Bulgarian historiography -- namely, that the Macedonian nation is a product of the Communist Third International, as well as the claims that the term „Macedonian44 was used as a geographical reference and that it is allegedly a construction of „Serbocommunist44 historians from Skopje, as a product of Macedonism under the aegis of Stoyan Novakovic. That these allegations are in large part arbitrary becomes clear from the facts supplied by official, relevant and competent official Bulgarian sources.
Keywords: MACEDONIA; MACEDONIANS; IDENTITY